WAKAF SEBAGAI SUMBER EKONOMI SYARIAH - Syukri, Mahmud; Bahri, Syaeful (Magister Manajement Studies Program, 2023)
Waqf is a source of funding that has the potential for community welfare. Several countries use waqf to support their economic development for the welfare of their people through productive development of their waqf programs between Turkey, Egypt, Jordan, and Malaysia, by carrying out developments in the sectors of research, education, health, poverty alleviation, and others. The Indonesian people understand that waqf is only limited to using immovable assets for less productive endowments, such as places of worship, educational institutions, etc. This has made the condition of waqf stagnant in Indonesia, even though Indonesia's potential for productive waqf is extraordinary as conveyed by the Vice President of the Republic of Indonesia who stated that the achievement of national cash waqf in 2022 was IDR 1.4 trillion or only 0.5% of the potential cash waqf of more than IDR 180 trillion. The existence of cash waqf is needed to facilitate the Muslim community in giving charity. Cash waqf is intended for places of worship and infrastructure and must also be empowered through productive waqf. Government support for community economic empowerment through the waqf program was proven in 2017 by appointing the Financial Services Authority (OJK) to establish a Micro Waqf Bank (BWM), which had obtained permission from OJK. Micro Waqf Banks have the concept of providing loans or financing to people who are not yet bankable or lack access to formal financial institutions such as banks. Even though the potential for waqf in Indonesia is enormous, in reality, the realization of waqf still needs to be improved due to several challenges.For this reason, the solution efforts are: a. carry out the development of good waqf governance, including implementing the Waqf Core Principles program and improving electronic-based waqf services; b. carry out HR competency upgrading on an ongoing basis; c. intensive socialization of waqf literacy and understanding to the public; d. carry out institutional harmonization and revision of waqf laws and regulations by increasing coordination between related agencies.